Biosafety characteristics and antibacterial activity of probiotic strains against Streptococcus mutans, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis - Jeong-Yong Park; Ji Yeon Lee; YongGyeong Kim; Byoung-Kook Kim; Byung Kwon Kim; Soo-Im Choi (Annals of Microbiology)
Abstract Background Oral diseases with high prevalence worldwide are recognized as severe health problems. Probiotics are used to prevent oral diseases, including dental caries, oral malodor, periodontitis, and subgingival plaque. In this study, we aimed to confirm the antibacterial effect of probiotics on oral pathogens and to assess their characterization and safety as probiotics. Methods The antibacterial effects of Lacticaseibacillus rhamnosus MG4706, Lacticaseibacillus paracasei MG4715, and Limosilactobacillus reuteri MG4722 on the growth biofilm formation of Streptococcus mutans, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis were evaluated. We also investigated the production of antibacterial substances (H2O2 and reuterin) by these strains and their ability to adhere to oral epithelial cells. The safety of L. reuteri MG4722 was verified through whole-genome sequencing analysis and antibiotic susceptibility, lactate dehydrogenase activity, hemolytic activity, and bile acid hydrolase activity. The reuterin biosynthesis genes of L. reuteri MG4722 were identified using genomic analysis. Results L. reuteri MG4722 significantly inhibited the growth of S. mutans, A. actinomycetemcomitans, and P. gingivalis and suppressed the biofilm formation by A. actinomycetemcomitans. In addition, it showed considerable adhesion ability to oral epithelial cells. L. reuteri MG4722 produced H2O2 and reuterin as antibacterial substances, as confirmed by the presence of genes encoding the antibacterial compounds reuterin, reuteran, and reutericyclin. L. reuteri MG4722 showed no hemolysis, bile salt hydrolase activity, antibiotic resistance or toxicity to HT-29 cells, and no antibiotic-resistance genes were identified. Conclusion L. reuteri MG4722 demonstrated antibacterial effects on oral pathogens by producing antibacterial substances and adhering to oral epithelial cells. These results suggest that L. reuteri MG4722 could be an effective probiotic for oral health.